ISLAM DI IRAN: Dari Era Umar ibn al-Khattāb Hingga Ahmadinejad - ., Asmullah (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem in this paper is trying to study or elaborate in depth about Islam in Iran from the era of Umar ibn Khattāb to Ahmadinejad. To answer this problem, the author tries to trace, explore and analyze several books, books, opinions of historians and various related writings in order to obtain a deeper and more accurate understanding.The results of the study of this paper show that during the leadership of Caliph Umar ibn al-Khattab (634-644 AD), the territory of the Persian Empire (Iran) began to be conquered in various battles. From 634 AD to 820 AD, the territory of Persia (Iran) was successively under the rule of the Khulafa' al-Rasyidin, the Umayyad dynasty, and the Abbasid dynasty. If one contemplates or examines the long span of Islamic history in Persia (Iran), the Persians (Iran) have played and contributed quite a bit, both in terms of the spread of Islamic teachings to the Eastern parts of the world, as well as in terms of the development of Islamic culture and civilization. . The spread and expansion of Islamic territory to the eastern world cannot be separated from the role of Iran which is at the gate of the eastern world. This can be seen from the entry of Islam into Persia, Armenia, Azerbaijan, Turkistan, Turkmenistan, Pakistan, Afghanistan, India, China, Malaysia and Indonesia. Persia (Iran) as an Islamic country which has privileges from various interesting aspects to study and elaborate on even when Ahmadinejad was elected as president he was one of those people who lived a simple life. He is also known as a conservative figure who is very loyal to the values ​​of the Islamic Revolution in Iran.Islam, Iran, History, Umar Ibn al-Khattab,Ahmadijenad